2022
DOI: 10.1148/radiol.2021210986
|View full text |Cite|
|
Sign up to set email alerts
|

Chest Radiograph Scoring Alone or Combined with Other Risk Scores for Predicting Outcomes in COVID-19

Abstract: Key Results1. Among a 787-patient cohort with confirmed COVID-19, three chest radiograph scores (BRIXIA, RALE, and percent opacification) all had good interrater reliability with intraclass correlations of 0.87, 0.86, and 0.72 respectively.2. Radiograph scores predicted intensive care unit (ICU) admission or death after COVID-19 diagnosis. A 50%-75% opacification (compared to 0%-25%) associated with a 2.2-fold increase in these outcomes among those eligible for ICU care after adjustment for clinical risk scori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 37 publications
2
39
1
Order By: Relevance
“…We cannot confirm that, because our median admittance (A) Brixia score was over 11.3 in spring and over 8 in autumn patients; from there, it went higher to the Brixia H (highest) score. Balbi [ 43 ], d’Souza [ 44 ] and Au-Yong [ 45 ] correlated the Brixia A score with outcomes in COVID-19 patients. Setiawati [ 46 ] found that severe cases of COVID-19 pneumonia had a Brixia score over 6, Gatti [ 47 ] over 7 upon admission and Boari [ 48 ] over 8, but the first and last authors did not specify which Brixia score they used: A, H or E. Similarly, Hoang [ 49 ] and Gurtoo [ 50 ] also correlated Brixia score with the outcomes in COVID-19 patients but did not specify which Brixia score they used in calculations—either A, H or E score—or if there was more than one chest X-ray taken of each patient.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot confirm that, because our median admittance (A) Brixia score was over 11.3 in spring and over 8 in autumn patients; from there, it went higher to the Brixia H (highest) score. Balbi [ 43 ], d’Souza [ 44 ] and Au-Yong [ 45 ] correlated the Brixia A score with outcomes in COVID-19 patients. Setiawati [ 46 ] found that severe cases of COVID-19 pneumonia had a Brixia score over 6, Gatti [ 47 ] over 7 upon admission and Boari [ 48 ] over 8, but the first and last authors did not specify which Brixia score they used: A, H or E. Similarly, Hoang [ 49 ] and Gurtoo [ 50 ] also correlated Brixia score with the outcomes in COVID-19 patients but did not specify which Brixia score they used in calculations—either A, H or E score—or if there was more than one chest X-ray taken of each patient.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Further CT findings included consolidation, linear opacities, reversed halo sign, and crazy-paving sign [ 5 , 6 , 8 10 , 13 ]. The definitions of these CT findings were based on the uniform terms for thoracic imaging by the Fleishner society [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Numerous clinical and imaging markers of disease severity have been reported. Among imaging markers, computed tomography (CT) provides the most sensitive radiological technique for the diagnosis of COVID-19, revealing diffuse lung alterations, ranging from ground-glass opacity to consolidation [ 5 10 ]. In addition, different radiological lung patterns are manifested over the course of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of CXR helps to predict COVID-19 outcomes, especially with the presence of CXR reporting systems, such as Brixia, and Radiographic Assessment of Lung Edema (RALE), 23 which helped to predict the negative outcomes of the disease, reliably. In addition, using the CXR severity score may help in decision-making regarding the most suitable admission department.…”
Section: Introductionmentioning
confidence: 99%